Die Schwedische Akademie und der Nationalsozialismus - Paulus Tiozzo (Moderna Språk)
This article is an empirical study of the reception of National Socialism by a selection of members of the Nobel Committee of the Swedish Academy. Its purpose is firstly to offer an explanation how impressions of the German political field during the 1920s and 1940s affected the evaluation of German Nobel Prize candidates. Secondly, it offers a critical overview of the ambivalent relationship that the members had to the Nazi ideology. Although they were all essentially critical, they sympathised with certain elements of it, including a fascination for Adolf Hitler. All these conclusions are derived from an analysis of original documents, including letters, reviews, reports and protocols from the archives of the Swedish Academy.